Homologous recombination enhances radioresistance in hypopharyngeal cancer cell line by targeting DNA damage response. (January 2020) - Liu, Chuan; Liao, Kui; Gross, Neil; Wang, Zhihai; Li, Guojun; Zuo, Wenqi; Zhong, Shixun; Zhang, Zixin; Zhang, Hua; Yang, Jianming; Hu, Guohua
Highlights: Homologous recombination (HR) pathways play important roles in radioresistant in hypopharyngeal carcinoma. The levels of key proteins in HR pathways are overexpressed both in vitro and in vivo in hypopharyngeal carcinoma. Silencing RPA1 reduces the radioresistance of hypopharyngeal carcinoma. Proteins in HR pathways may be potential biomarkers to predict hypopharyngeal carcinoma response to radiotherapy. Abstract: Background: Radiotherapy is a central treatment option for hypopharyngeal squamous cell carcinoma, but the prognoses of patients treated with radiotherapy only are not satisfactory due to radioresistance. The underlying molecular mechanisms remain largely elusive, and mechanism-derived predictive markers of radioresistance are currently unavailable. Methods: In this study, we first established a specifically radioresistant FaDu cell line by repeated exposure to ionizing radiation with a total dose of 60 Gy (FaDu-RR). The validation of FaDu-RR cells was performed by clonogenic cell survival assay and cell proliferation assay. Microarrays and bioinformatics were analyzed to determine the differentially expressed mRNAs and their functions. DNA-repair capabilities were tested by cell cycle analysis and comet assay. The expressions of four key proteins in homologous recombination pathways, including BRCA1, BRCA2, RPA1, and Rad51, were detected both in FaDu-RR cells and radioresistant xenograft. Results: We established the specifically radioresistant FaDu cell line. Through microarrays and bioinformatics, homologous recombination pathways were suggested to play important roles in radioresistant mechanisms. High expression levels of key proteins in homologous recombination pathways were then detected both in FaDu-RR cells and radioresistant xenograft. Silencing RPA1 could reduce the radioresistance of FaDu-RR cells. Conclusion: Our results provided strong evidence that homologous recombination enhances the radioresistance in hypopharyngeal carcinoma. Proteins in homologous recombination pathways may be potential biomarkers to predict hypopharyngeal carcinoma response to radiotherapy, establishing a basis for their utility in clinical practice.